Branding: how it works and why it matters - Lauterborn, Robert F. (Henry Stewart Talks, 2014)
Core concept of marketing, BCG portfolio analysis tool, Value of a strong brand, de Bono's three stages of business, Brand positioning, How to build a strong brand, Company vision and brand purpose, Marketing myopia, How to lose a strong brand, Kotler 4P's vs. Lauterborn 4C's, Value proposition criteria, The power of a strong brand